Platelet CD40L at the interface of adaptive immunity - Elzey, Bennett D.; Ratliff, Timothy L.; Sowa, Jennifer M.; Crist, Scott A. (Thrombosis research, 2011)
Initiated by the finding that platelets express functional CD40 ligand (CD40L, CD154), many new roles for platelets have been discovered in unanticipated areas, including the immune response. When current literature is considered as a whole, the picture that is emerging begins to show that platelets are able to significantly affect, for better or worse, the overall health and condition of the mammalian host. Animal models have made significant contributions to our expanding knowledge of platelet function, much of which is anticipated to be clinically relevant. While still mostly circumstantial, the evidence supports a critical role for CD40L in many normal and disease processes.